2020
DOI: 10.3174/ajnr.a6665
|View full text |Cite
|
Sign up to set email alerts
|

Manganese-Enhanced MRI in Patients with Multiple Sclerosis

Abstract: BACKGROUND AND PURPOSE: Cellular uptake of the manganese ion, when administered as a contrast agent for MR imaging, can noninvasively highlight cellular activity and disease processes in both animals and humans. The purpose of this study was to explore the enhancement profile of manganese in patients with multiple sclerosis. MATERIALS AND METHODS: Mangafodipir is a manganese chelate that was clinically approved for MR imaging of liver lesions. We present a case series of 6 adults with multiple sclerosis who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…However, mangafodipir may release uncomplexed Mn(II) ion in regions of neural activity for uptake into active brain regions in human 90 . Mangafodipir safely identified plaques in human multiple sclerosis 91 . Application of MEMRI to nonbrain tissue, such as non‐CNS organs in mouse, 347 cardiac muscle in human, 134,348 and diagnoses for cancer, 131,132,349 as well as others mentioned in Section 5.1, are emerging.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, mangafodipir may release uncomplexed Mn(II) ion in regions of neural activity for uptake into active brain regions in human 90 . Mangafodipir safely identified plaques in human multiple sclerosis 91 . Application of MEMRI to nonbrain tissue, such as non‐CNS organs in mouse, 347 cardiac muscle in human, 134,348 and diagnoses for cancer, 131,132,349 as well as others mentioned in Section 5.1, are emerging.…”
Section: Discussionmentioning
confidence: 99%
“…90 Mangafodipir safely identified plaques in human multiple sclerosis. 91 Application of MEMRI to nonbrain tissue, such as non-CNS organs in mouse, 347 cardiac muscle in human, 134,348 and diagnoses for cancer, 131,132,349 as well as others mentioned in Section 5.1, are emerging. Analogies of brain-wide activity using functional atlases to compare rodent networks with human networks obtained by fMRI are more likely than invasive techniques such as high-density electrode arrays or optogenetic manipulations to lead to translation of mechanistic knowledge from preclinical to human disease states.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The centripetal DCE pattern, seen only in a percentage of new lesions, temporally follows the centrifugal pattern, but not vice versa ( Gaitán et al, 2011 ). Interestingly, a recent study using an intravenous manganese-based contrast agent, mangafodipir, found that manganese ions enable visualization of acute white matter lesions and their surrounding white matter, with persistent enhancement for an extended period relative to gadolinium-based contrast material ( Suto et al, 2020 ). This persistent enhancement is thought to be due to the intracellular uptake of manganese ions released from mangafodipir, compared to the gadolinium agents, which are restricted to the interstitial and intravascular compartments.…”
Section: Imaging New Inflammatory White Matter Lesionsmentioning
confidence: 99%